The unifying catalytic mechanism of the RING-between-RING E3 ubiquitin ligase family - Xiangyi S. Wang; Thomas R. Cotton; Sarah J. Trevelyan; Lachlan W. Richardson; Wei Ting Lee; John Silke; Bernhard C. Lechtenberg (Nature Communications, 2023)
RBR E3 ubiquitin ligases utilise a 2-step catalytic mechanism previously defined for only few of the RBR family members. Here, the authors examine the poorly studied RBRs HOIL-1 and RNF216 to define general principles of RBR catalysis and regulation and identify specific functional differences.